EFFICIENCY OF ECONOMIC RELATIONS OF UZBEKISTAN AND TURKEY (American Journal of Interdisciplinary Research and Development, 2024)
Based on the principles of absolute, relative and competitive advantages of international trade, the countries of Uzbekistan and Turkey, relying on their economic, financial, technical and resource potential, are striving to increase the effectiveness of further expansion and improvement of their foreign economic relations. Uzbekistan has been demonstrating to the world public that Turkey is important in ensuring peace, stability and cooperation in the region and the world.